POLITIK HUKUM PENGATURAN PAJAK RUMAH KOS DALAM UPAYA PENINGKATAN PENDAPATAN DAERAH DI KOTA PEKANBARU - Putri, Mike Dwi; Firdaus, Emilda; Diana, Ledy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
The implementation of boarding house tax is regulated in Regional Regulation Number 7 of 2018 concerning Amendments to Regional Regulation Number 7 of 2011 concerning Hotel Tax. In Article 2 paragraph 4 of the tax that boarding houses are included as tourist objects, the number of rooms is more than 10 (ten) rooms. Article 3 paragraph 3 of the tax on boarding house tax is 2.5% (two point five percent) of the basic imposition. Whereas before the change in the regional regulation the tax rate for boarding houses was 5% (five percent) of the basic imposition. Understanding, the criteria for boarding houses and others regarding boarding house management are not really detailed in the regional regulation, it also makes people confused about the regional regulations and in the end they do not register as taxpayers, therefore there are still many boarding houses that have not been registered. as a taxpayer, it will certainly affect the decline in regional income including a reduced boarding house tax rate. Therefore, the problems that need to be examined in this study are how the law of boarding house tax regulation in an effort to increase local income in Pekanbaru City, and what is the ideal tax arrangement regarding boarding house tax.This research is a normative research, where normative legal research is carried out by examining library materials or secondary data consisting of primary, secondary and tertiary legal materials. This study examines the problems in accordance with the scope of the problem. The approach to law is carried out by regulating statutory regulations and regulations related to the legal issues under study. In this study, the authors conducted research on the legal principles in ordering, the regulations, namely the principle of legal certainty, the principle of kinship, and also the principle of openness.From the research results, it is known that the regulations formed in the regions are called legal politics, which are state legal policies to achieve national goals by forming laws to foster matters that are directly related to national interests. Legal politics (policies) regarding changes or regulations regarding boarding house taxes must include the creation of a boarding house concept, the criteria for a boarding house, its tax arrangement or tax collection flow, and general matters regarding boarding house management. The making of invitation rules must also be in accordance with principles such as the principle of legal certainty, the principle of kinship, and the principle of openness.Keywords: Political Law – Formation of Legislation – Boarding House Tax